(untitled) (REMUNOM, 2025)
Health education represents a significant responsibility within the responsibilities of health professionals, especially Health Surveillance. Health and education are closely linked, fundamental for the advancement of health surveillance strategies. Unfortunately, many people perceive VISA’s actions mainly as imposing punishments and sanctions, rather than as a service to protect public health. It is important that individuals and groups understand the importance of health surveillance. Health surveillance awareness plays an important role in promoting public health. to the study, it is highlighted that it consists of qualitative research, presenting as a method of approach the descriptive research of bibliographical review, having brought together the main works referring to the proposed theme with the objective of analyzing the relevance of education in health surveillance, of in order to demonstrate how education can enhance the development of health surveillance and its actions in the construction of quality public health based on the well-being of society.